2016
DOI: 10.3109/14767058.2016.1141887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal obesity on the fetal electrocardiogram during labor

Abstract: Obesity might not influence the fetal electrocardiogram during labor as an independent risk factor for adverse pregnancy outcomes. Studies with larger cohort sizes are needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
3
0
5
Order By: Relevance
“…It was suggested that more weight gain than recommended and maternal obesity increased the complications such as induction in labor (Pevzner et al, 2009, Majumdar et al, 2010, Wolfe et al, 2011), episiotomy application (Kabiru and Raynor, 2004, Racz et al, 2016), interventional vaginal delivery (Wolfe et al, 2011, Marchi et al, 2015, Racz et al, 2016), and non-progressive action (Vahratian et al, 2005). Similarly, our study also showed that the rate of induction, episiotomy, and interventions at vaginal birth in pregnancies with mild obesity and obesity were higher than those in normal weight pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that more weight gain than recommended and maternal obesity increased the complications such as induction in labor (Pevzner et al, 2009, Majumdar et al, 2010, Wolfe et al, 2011), episiotomy application (Kabiru and Raynor, 2004, Racz et al, 2016), interventional vaginal delivery (Wolfe et al, 2011, Marchi et al, 2015, Racz et al, 2016), and non-progressive action (Vahratian et al, 2005). Similarly, our study also showed that the rate of induction, episiotomy, and interventions at vaginal birth in pregnancies with mild obesity and obesity were higher than those in normal weight pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Az urológiai-reprodukciós zavarok köre szintén jelentős (vizeletincontinentia, polycystás ovarium szindróma, terhességi cukorbetegség, gyakoribb vetélés, a koraszülések nagyobb aránya). Ennél a betegcsoportnál a terhesgondozás időszakában szorosabb megfigyelésre van szükség [9]. Az elhízás mintegy 13 anatómiai lokalizáció tekintetében daganatos betegségek kialakulásának fokozott rizikójával jár [10].…”
Section: Eredeti Közleményunclassified
“…Ehhez a valós idejű EKG-analízist lehetővé tévő STAN magzati monitorrendszert használtuk. 60 obes beteg adatait hasonlítottuk össze 108, normál testalkatú várandósnál mért eredményekkel, és arra jutottunk, hogy az anya kóros elhízása önmagában nincs hatással a magzati szív elektrofiziológiai jellemzőire [23].…”
Section: A Várandósság éS a Kóros Elhízás Hatása Az Anyai Keringésreunclassified